2020
DOI: 10.1039/d0en00686f
|View full text |Cite
|
Sign up to set email alerts
|

Improving the utilization rate of foliar nitrogen fertilizers by surface roughness engineering of silica spheres

Abstract: Compared with root nitrogen fertilization, foliar nitrogen fertilizer (FNF) has been widely used for crops growth due to its fast fertilizer efficiency and high utilization rate, especially when the crops...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Another interesting work by Li et al [84] considered maize and micro-nanostructured silica spheres (solid silica spheres (S-Si), hollow silica spheres (H-Si) and sea urchin-like micro-nanostructured hollow silica spheres (SUH-Si,~500 nm) with different surface roughness and morphologies as carrier for N to improve the adhesion capacity on plant leaves when applied as foliar fertilizers. Results indicated that SUH-Si-N provide nitrogen nutrition for maize seedlings and promote their growth and development.…”
Section: Si Nanoparticles As Plant Nutrient Carriermentioning
confidence: 99%
“…Another interesting work by Li et al [84] considered maize and micro-nanostructured silica spheres (solid silica spheres (S-Si), hollow silica spheres (H-Si) and sea urchin-like micro-nanostructured hollow silica spheres (SUH-Si,~500 nm) with different surface roughness and morphologies as carrier for N to improve the adhesion capacity on plant leaves when applied as foliar fertilizers. Results indicated that SUH-Si-N provide nitrogen nutrition for maize seedlings and promote their growth and development.…”
Section: Si Nanoparticles As Plant Nutrient Carriermentioning
confidence: 99%
“…These results demonstrated that the contact angles of NanoSi-CDs on the maize leaf surface were smaller than those of CDs. Because the aldehyde group of formaldehyde and the hydroxyl group of resorcinol are highly hydrophilic, they contribute to increased wettability of the material. , Moreover, NanoSi could greatly reduce the possibility of material slipping from the leaf surface, thereby increasing its bioavailability . For instance, the conventional nitrogen fertilizer showed a 73.3% decrease in the contact angle when loaded with NanoSi, resulting in a 2.3 times increase in the utilization rate …”
Section: Resultsmentioning
confidence: 99%
“…54,55 Moreover, NanoSi could greatly reduce the possibility of material slipping from the leaf surface, thereby increasing its bioavailability. 56 For instance, the conventional nitrogen fertilizer showed a 73.3% decrease in the contact angle when loaded with NanoSi, resulting in a 2.3 times increase in the utilization rate. 49 Meanwhile, the SFE of the maize leaves was calculated by the Owens−Wendt−Rabel−Kaelble method, 57 using the contact angle of two test liquids (Table S2).…”
Section: High Foliage Adhesion On the Leaf Surfacementioning
confidence: 99%
“…Studies have shown that nanomaterials can enter plant cells by binding to carrier proteins, through ion channels, or endocytosis [ 59 , 60 ]. The gravitates can be more uniformly encapsulated with reagents after they are uniformly dispersed by the irradiation technique [ 61 ].…”
Section: Resultsmentioning
confidence: 99%